Quantificação e identificação de Vibrio spp. na hemolinfa de camarões Litopenaeus vannamei cultivados em fazendas no Estado do Ceará - Carvalho, Edirsana Maria Ribeiro de (2009)
Most of shrimp bacterial infections are caused by Vibrio bacteria genus. This study aims to quantify identify Vibrio in the hemolymph of the marine shrimp Litopenaeus vannamei cultivated in farms in State of Cear, Brazil. Related is also the time of coagulation of hemolymph with counts of Vibrio. Sixteen samples were performed on four farms (A, B, C and D), eight shrimps with 4 g, and eight with eight grams shrimps. The collections were made in seasonal periods: rainy and drought. A total of 480 samples, and 240 to shrimps with 4 g and 8 g each, respectively. The values in the Standard Plate Count (SPC) of total vibrio, Vibrio Suc+ and Suc- in the hemolymph of shrimp samples with 4 g, in the rainy season ranged from: 2. 74 x 10⁴ to 28.70 x 10⁶ CFU/mL (est.), <6.0 to 14.64 x 106CFU/mL and <6.0 to 12.72 x 106 CFU/mL, respectively. For hemolymph of shrimp with 8 g of the SPC and the total Vibrio Suc+ and Sucranged from 1.68 x 10⁴ to 15.18 x 10⁶ CFU/mL (est.), <6.0 to 1.8 x 105 CFU/mL and <6.0 to 15.18 x 106CFU/mL (est). During the period of drought for these values of shrimp haemolymph of four grams, were: 9.0 x 10² (est.) to 5.40 x 104 CFU mL total Vibrio, <6.0 to 1.71 x 10⁴CFU/mL (Suc-) and <6.0 to 5.40 x 104 CFU/mL (Suc+). For shrimp with 8 g a total Vibrio count was 9.0 x 10² (est.) CFU/mL to 2.0 x 10⁷, <6.0 to 4.02 x 106 CFU/mL (Suc-) and <6.0 to 2.0 x 10⁷CFU/mL (est.) (Suc+). The results show that the rates of colonies of Vibrio Suc- and Suc+ were higher in the rainy season than in the drought. There was no relationship between the time of coagulation and the counts of Vibrio in the hemolymph of shrimps. The species that predominated in the period were: V. coralliilyticus, V. parahaemolyticus, Vibrio pelagius II, Vibrio alginolyticus, Vibrio mediterranei, Vibrio mimicus, Vibrio vulnificus B1